PENGUATAN KELEMBAGAN KADER POSYANDU DALAM PENCEGAHAN DAN PENANGANAN STUNTING DI KENAGARIAN AIE TAJUN KECAMATAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Metha Kemala Rahayu Syafwan; Maidawilis Maidawilis; Putri Minas Sari; Ridhyalla Afnuhazi; Yanti Nopita (Ensiklopedia Research and Community Service Review, 2025)
The government is aiming to reduce stunting rates by 26% by 2025. To that end, the government continues to strive to achieve this 2025 target by improving the performance of accelerating stunting reduction across all regions in Indonesia. The Head of the West Sumatra Health Office also emphasized that the province of West Sumatra is serious about preventing stunting, including Padang Pariaman Regency. Lubuk Alung still has a stunting rate of 64 toddlers (2.4%), including in Aie Tajun village, a village known for its extensive rice fields. So far, the government's program for developing stunting prevention in Aie Tajun Village District has been implemented, but the stunting rate has not been resolved. The purpose of community service is to strengthen the institutionalization of integrated health post (Posyandu) cadres. With this effort, it is hoped that good Posyandu management can improve community welfare. The methods in this service include FGDs, training, mentoring, and evaluation. The partners of this community service are 16 toddler mother cadres and 9 pregnant women and mothers of toddlers. The results of the community service found a commitment from toddler cadres and the village government to prevent stunting by providing counseling on anti-stunting foods. The existence of an anti-stunting pilot house and the cadres were able to perform anthropometric measurements correctly and create a WHO curve to determine whether a child was stunted or not. With the implementation of this activity, it is hoped that the village will support the development of this program.Keywords: toodlers, stunting, cadres, posyandu